Vascular plants and vegetation of the Tepecapa gully in the municipality of Tlayacapan, Morelos, Mexico - Hernández Cárdenas, Rodrigo Alejandro; Cerros Tlatilpa, Rosa; Flores Morales, Alejandro (Instituto de Ecología, A.C., 2014)
The study area, the Tepecapa gully with an approximate length of 3.5 km, is situated in the core zone of “Las Mariposas” in the Biological Corridor Chichinautzin in the state of Morelos. Periodic collections were made over a year and a half, from October 2009 to April 2011. We collected 1018 specimens of Pteridophytes and relatives, Gymnosperms, and Angiosperms, belonging to 99 families, 266 genera and 434 species. The families Asteraceae, Fabaceae, Poaceae, Orchidaceae, Pteridaceae, Solanaceae and Bromeliaceae are the best represented ones. Three types of vegetation are reported and described for the study area. Two genera (Amyris and Dasylirion) and 16 species are new records for the state of Morelos.